Plato's Phaedo : Selected Papers from the Eleventh Symposium Platonicum - Cornelli, Gabriele; Robinson, Thomas M.; Bravo, Francisco (Academia-Verlag, 2018)
The enclosed Proceedings are a selection, by 41 of the Society's scholars, of the papers presented at the Eleventh Symposium Platonicum of the International Plato Society, held in Brasilia, Brazil, under the auspices of the University of Brasilia. The volume covers all major issues related to the interpretation of Plato's Phaedo and the reception of this central dialogue throughout Antiquity.Six main chapters examine different aspects concerning the dialogue, starting with its structure, moving on to topics of Myth, Emotion and Virtues. Special focus is laid on the Phaedoís core issue: The soul and the images of afterlife and immortality. Chapter five the moves on to the manifestation of specific argumental structures. The book concludes with a focus on historiographical content, Socrates as depicted in the Phaedo.